2018
DOI: 10.1016/j.rboe.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

A study on the prevalence of the anconeus epitrochlearis muscle by magnetic resonance imaging

Abstract: ObjectiveTo analyze magnetic resonance imaging (MRI) of the elbow area to quantify the presence of the anconeus epitrochlearis muscle.MethodsA total of 232 exams were analyzed; 218 were included, of which 141 were of men and 77, women.ResultsPresence of the muscle was observed in 29 cases (13.3%), demonstrating that the presence of this muscle on images does not have a statistical correlation with the gender or age of the individual.ConclusionThe prevalence of the anconeus epitrochlearis muscle is variable, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…He found the muscle in 26 males and eight females and that it was bilateral in 15 males and four females [ 6 ]. Furthermore, a study done by Nascimento and Ruiz [ 1 ] found 29% of individuals have this muscle variation, and it was not associated with age or sex.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…He found the muscle in 26 males and eight females and that it was bilateral in 15 males and four females [ 6 ]. Furthermore, a study done by Nascimento and Ruiz [ 1 ] found 29% of individuals have this muscle variation, and it was not associated with age or sex.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of this muscle has clinical relevance in relation to the cubital tunnel syndrome. Some speculate it may be a cause of cubital tunnel syndrome, and others have suggested it is actually protective for the ulnar nerve [ 1 ]. Cubital tunnel syndrome is a common cause of ulnar nerve entrapment in the upper extremity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…58 For instance, the anconeus epitrochlearis is an accessory muscle at the medial epicondyle of the humerus at the cubital tunnel and can cause ulnar nerve compression and neuropathy in 15% of cases. 59 Other common accessory muscles include the extensor digitorum brevis manus on the dorsum of the hand, the accessory soleus in the posterior ankle (►Fig. 25), and the peroneus tertius and quartus in the lateral ankle.…”
Section: Variant Anatomy Accessory Musclesmentioning
confidence: 99%